Diabetic retinopathy relates to the incidence of foot ulcers and amputations in type 2 diabetes. Issue 3 (12th January 2023) - Borderie, Gauthier; Foussard, Ninon; Larroumet, Alice; Blanco, Laurence; Barbet‐Massin, Marie‐Amélie; Ducos, Claire; Rigo, Marine; Arab, Lila Rami; Domenge, Frédéric; Mohammedi, Kamel; Ducasse, Eric; Caradu, Caroline; et al.
Abstract: Aims: We investigated whether Diabetic Retinopathy (DR) is related to Diabetic Foot Ulcer (DFU) development, adjusted for the stratification of the International Work Group on Diabetic Foot (IWGDF) guidance. Materials and Methods: DR and IWGDF stratification was registered retrospectively in patients hospitalised from 2009 to 2017 for uncontrolled and/or complicated type 2 diabetes. New DFUs were registered until 2020. Survival analyses categorised the subjects for DR, and multivariate Cox regression adjusted for confounders. Results: The 522 patients (57.9% male) were 62 ± 9 years old with a diabetes duration of 14 ± 10 years, HbA1c of 8.7 ± 1.8%, 33.9% macroangiopathies and 44.8% diabetic kidney diseases. Their grades of DFU risk were 0 for 43.3%, 1 for 23.9%, 2 for 7.1%, and 3 for 25.6%. During the 52 months follow‐up (Inter Quartile Range: 32–71), 58 new DFUs and 18 lower‐limb amputations occurred, mostly in patients with DR present in 140 (26.8%) patients. Adjusted for age, sex and conventional risk factors (duration and control of diabetes, arterial hypertension, and dyslipidemia), and other complications (macroangiopathy and diabetic kidney disease), DR was associated with a greater incidence of DFUs. Adjusted for the IWGDF classification, DR was related to new DFUs (HR: 2.51, 95%Confidence Interval [CI]: 1.48–4.26) and amputations (HR: 3.56, 95%CI: 1.26–10.07). This relationship persisted in ascending IWGDF grades with incidences of DFUs from 2/1000 (grade 0, no DR) to 121/1000 patient‐years (grade 3 and DR) and amputations from 0 (grade 0, no DR) to 38/1000 patient‐years (grade 3 and DR). Conclusions: Diabetic retinopathy independently relates to the incidence of foot ulcers and amputations in patients hospitalised for type 2 diabetes.